The Effect of Maze Game Media and Learning Style on First-Grade Students’ Understanding of Number Concepts - Hety Nurendang; Mardiyana Mardiyana; Supianto Supianto (Journal of General Education and Humanities, 2026)
Students’ understanding of number concepts in early elementary grades varies, indicating the need for instructional media and approaches aligned with learners’ characteristics. This study aims to analyze differences in first-grade students’ understanding of natural number concepts based on learning styles (visual, auditory, and kinesthetic) using the Maze Game and number card learning media. A quantitative approach with a factorial experimental design was employed. The subjects were first-grade students from SDN WADAS 1 (experimental class) and SDN WADAS IV (control class). Data were collected using a natural-number concept comprehension test and a learning-style questionnaire. Data analysis was conducted using a two-way ANOVA to examine the effects of learning media, learning styles, and their interaction on students’ conceptual understanding. The results indicate significant differences in students’ understanding of natural number concepts, depending on learning style, across both learning media. Students with visual and kinesthetic learning styles achieved higher comprehension scores than those with auditory learning styles. Additionally, a significant interaction effect between learning media and learning styles was identified, suggesting that the effectiveness of instructional media depends on students’ learning style characteristics. Learning styles and instructional media significantly influence students’ understanding of natural number concepts. Instruction that integrates visual elements and physical activities is more effective in improving mathematics learning outcomes among early-grade elementary students. Therefore, teachers are encouraged to design adaptive learning strategies that accommodate diverse learning styles.